SKEMA DESENTRALISASI ASIMETRIS PASCA BERLAKUNYA UU CIPTA KERJA [The Decentralization Scheme after the Implementation of the Omnibus Law] - Fradhana Putra Disantara; Azzahra Ayu Sabilla; Raraniken Ayuning Bintari (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2021)
The problems of implementing decentralization and principle of centralization cause emergence the concept of asymmetric decentralization. The concept of asymmetric decentralization is believed to be able to handle and overcome various conflicts between central government and local governments. However, in Indonesia the implementation of asymmetric decentralization experienced dynamics idea after the enactment of Law Number 11 of 2020 concerning Job Creation law (Omnibus Law). This type of research is legal research. This study uses a statutory and conceptual approach by using primary and secondary legal materials. The two legal materials are inventoried to obtain a prescriptive legal analysis, as well as providing a holistic conceptual study of legal issues discussed. This legal research aims to analyze the dynamics of decentralization as the cause of the birth of asymmetric decentralization and analyze the implementation of asymmetric decentralization in Indonesia after enactment of Job Creation Law. The results of this study stated that the idea of asymmetric decentralization was caused by failure of implementation of the key to success of decentralization. Furthermore, the implementation of asymmetric decentralization was reduced by the introduction of the Job Creation Law, because of the presence of various provisions in the Job Creation Law which tend to be oriented towards re-centralization. Suggestions that can be done is to conduct a material test on various provisions that include a “greater” authority of the central government in the asymmetrical decentralized regional autonomy circles.Bahasa Indonesia Abstrak: Problematika penerapan desentralisasi dan asas sentralisasi menyebabkan munculnya konsep desentralisasi asimetris. Konsep desentralisasi asimetris dipercaya dapat menangani dan menanggulangi berbagai konflik antarpemerintah pusat dengan pemerintah daerah. Meskipun demikian, di Indonesia implementasi gagasan desentralisasi asimetris mengalami dinamika pasca berlakunya Undang Nomor 11 Tahun 2020 tentang Cipta Kerja (UU Ciptaker) atau Ominbus Law. Jenis penelitian ini adalah penelitian hukum. Penelitian ini menggunakan pendekatan perundang-undangan dan konseptual dengan menggunakan bahan hukum primer dan sekunder. Kedua bahan hukum tersebut diinventarisasi untuk mendapatkan analisis hukum yang bersifat preskriptif, serta memberikan studi konseptual holistik tentang masalah hukum yang dibahas. Penelitian hukum ini bertujuan untuk menganalisis dinamika desentralisasi sebagai sebab lahirnya desentralisasi asimetris, serta menganalisis penerapan desentralisasi asimetris dalam otonomi daerah di Indonesia pasca berlakunya UU Ciptaker. Hasil penelitian menyatakan bahwa gagasan desentralisasi asimetris disebabkan kegagalan dari implementasi dari kunci keberhasilan desentralisasi. Selanjutnya, penerapan desentralisasi asimetris direduksi dengan hadirnya UU Ciptaker, oleh sebab hadirnya berbagai ketentuan dalam UU Ciptaker yang cenderung berorientasi pada resentralisasi. Saran yang dapat diberikan adalah melakukan uji materil mengenai berbagai ketentuan yang mencantumkan kewenangan pemerintah pusat secara “lebih besar” dalam pusaran otonomi daerah desentralisasi asimetris.